ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN SUKARELA INTERNET FINANCIAL REPORTING Pada Perusahaan yang Terdaftar Di Bursa Efek Indonesia pada tahun 2019 - Melisa Sofiana; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of company characteristics on voluntary disclosure of Internet Financial Reporting. The dependent variable used in this study is voluntary disclosure of Internet Financial Reporting. Company characteristic is proxied by Company Size, Profitability, Company Age, Internationalized company, and industrial sector are used as independent variables.The population used in this study is manufacturing company listed on the Indonesian Stock Exchange in the period of 2019. Total sample of companies amouned to 124 samples were taken by using purposive sampling method and data analysis is done by using the multiple linear regression.Based on the results of the study, it shows that company size, profitability, company age and internationalized companies have no effect on voluntary disclosure of Internet Financial Reporting. Meanwhile, the industrial sector has a significant positive effect on voluntary Internet Financial Reporting disclosure. This is because industrial sector companies are companies that are advanced and keep up with the times that have used services with internet media.